Feasibility study of using porous metal as practical shielding material - Ling, Y. (2010)
This paper presents the feasibility study of using porous metal for electromagnetic shielding purposes. Using the highly porous aluminum (close to 90% porosity) as the material under study, its shielding effectiveness (SE) was studied systematically. A preliminary measurement was carried out to evaluate the SE of porous aluminum sample. This was followed by a full-wave EM modeling of the porous aluminum shielded box. Finally, a shielded enclosure was assembled using porous aluminum panels and the overall SE of this enclosure was measured. With the conventional installation method, the enclosure has been found to provide at least 60 dB shielding effectiveness in the frequency range of 250 kHz to 1 GHz.